Segmented arch or continuous arch technique? A rational approach - Caldas, Sergei Godeiro Fernandes Rabelo; Ribeiro, Alexandre Antonio [UNESP]; Simplício, Hallissa; Machado, André Wilson (FapUNIFESP (SciELO), 2014)
This study aims at revising the biomechanical principles of the segmented archwire technique as well as describing the clinical conditions in which the rational use of scientific biomechanics is essential to optimize orthodontic treatment and reduce the side effects produced by the straight wire technique. © 2014 Dental Press Journal of Orthodontics.
Keywords: Biomechanics; Corrective Orthodontics; Orthodontics